(untitled) (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
This study analyses the diff erent modalities of professional development for the puppeteer, highlighting that, while in the past this took place through practice, today this training also takes place in universities which off er academic degrees in the profession. The article points out that currently one of the challenges in the training of puppeteers is to familiarize them with the knowledge produced by old masters and to stimulate them to seek out their own creative path. From this point of view, the article situates the training currently in progress at the Bialystok School in Poland, where the author is a lecturer. Keywords: Puppet theatre; professional development; puppeteer.